Объяснение:
1. 1,5 • 62 – 23=93-23=70.
***
2. 1) x^8 • x^2; =x^(8+2)=x^10;
2) x^8 : x^2=x^(8-2)=x^6;
3) (x^8)^2=x^(8*2)=x^16;
4) ((x^4)^5 • x^2)/x^12=x^(4*5)*x^2/x^12=x^(20+2)/x^12=x^(22-12)=x^10.
***
3. 1) –3*a^2*b^4 • 3a^2 • b^5= -9*a^4*b^9;
2) (–4a^2*b^6)^3=(-4)^3*(a^2)^3*(b^6)^3= -64a^6*b^18.
***
4. (5x^2 + 6x – 3) – (2x^2 – 3x – 4) = 5x^2 + 6x – 3 – 2x^2 + 3x + 4 =3x²+9x+1.
***
5. 1) (46 • 29) / 324=1334/324=4 38/324=4 1/162 ;
2) (2 2/3)^5 • (3/8)^6=(8/3)^5*(3/8)^6=(8/3)^5*(8/3)^(-6)=(8/3)^(-1)=3/8.
***
6. 125а^6b^3 • (–0,2a^2b^4)^3= 125*(-0,2)^3*a^6*b^12 = =-125*0,008*a^6*b^12=a^6*b^12.
2) 2xy² -18x =2x(y² -9) =2x(y -3)(y +3)
3) x^3 -64x =0
x(x² -64) =0
x=0
x²-64=0, (x-8)(x+8)=0
x-8=0, x=8
x+8=0, x= -8
ответ: x= -8, x=0, x=8
4) x+5=3x+9
x -3x =9-5
-2x =4
x = -2
5) 3b -(5b -1) +(b +4) =3b -5b +1 +b +4 =5 -5b +4b =5 -b